PENGARUH RASIO KEUANGAN, PENERAPAN PSAK 50 & 55 (REVISI 2006), MANAJEMEN LABA DAN PERANAN GOOD CORPORATE GOVERNANCE TERHADAP RETURN SAHAM - Rahil I. Aprilian; Yvonne Augustine (Jurnal Magister Akuntansi Trisakti, 2014)
We  examine  the  effects  of  financial  ratios,  implementation  of  PSAK  50  and  55 (Revised 2006), Earning Management and the Role of Good Corporate Governance (GCG) on Stock  Return.  The financial  ratios used  in this research  are Capital Adequacy  Ratio (CAR), Percentage of Operating Expense to Operating Revenue and Loan to Deposit Ratio (LDR). Earning management is measured by allowance for impairment losses and GCG as variable  that  moderated  earning  management  and  stock  return,  this  research  also  used dummy variable for implementation of PSAK 50 and 55. This research used 26 listed banking companies in Indonesia Stock Exchange from 2008 to 2011. Total observation of research is 80 years financial statements. The result showed that (1) the financial ratio that has significant influence on stock return is CAR; (2) earning management and GCG didn’t have significant influence on stock return, but the earning management that moderated by GCG has significant influence on stock return; (3) implementation  of PSAK 50 and 55 didn’t have significant influence on stock return; (4) All variable simultaneously made significant influence on stock return at 10% error.